Key Success Factors for 5G Technology Commercialization in Telecommunication Company Case Study of an Established XYZ Company in Indonesia - Hutajulu, Sahat; Dhewanto, Wawan; Prasetio, Eko Agus; Rudito, Priyantono (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. Technology commercialization is the long process to bring technology from the research domain into the commercialization area to end-users with monetizing purposes. This study analyzes critical success factors for 5G technology commercialization in an established company in Indonesia. By defining the most significant factors, a company can strategize the most effective investments to important factors only and avoid other less meaningful areas. 5G is approaching fast, and some of the major early adopters Mobile Network Operators (MNO) have already deployed 5G within this year. However, some other MNOs or telecom companies, in general, remain skeptical, considering the wide range of new business cases, the readiness of industries, and twice significant capital investment compare to predecessor technology 4G. This study is based on interpretivism philosophy and uses Qualitative semi-structured in-depth interviews, observation, and deductive scenario planning as the methodology. Use cases, innovation ecosystem, and technology complementary are found to be the key success factors for 5G commercialization in an established company. The novelty of this study is to identify the key success factors for technology commercialization specific for the 5G technology context in Indonesia. Three axes deductive scenario planning using critical success factors as the uncertainties are considered as the originality of this study.Keywords:  Key success factors, technology commercialization, established company, 5G